Fa`āliah Ijrā’ aṭ-Ṭarīqah al-Istiqrāiyyah Bi Uslūb STAD Wa Wasīlah Biṭāqah al-As’ilah Wa al-Ajwibah Li Tarqiyah Qudrah aṭ-Ṭalabah Fī Ta`allum an-Naḥw (Dirāsah Tajrībiyah Bi Ma`had `Ulūm al-Qur’ān Aceh Besar) - Rita Musfira; Mukhlisah Mukhlisah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Qawaid nahwu is one of the most important aspects in learning Arabic, which is related to determining the function of each word in a sentence, as well as giving the final tashkeel of each word and explaining the function of each word based on its position in a sentence.To achieve success in the learning process, a teacher is required to use methods, techniques, and teaching media to achieve learning objectives. Based on the research observation at the Ulumul Qur'an Boarding School in Aceh Besar, the researcher found that the nahwu teacher at the pesantren used the book Al-Nahwu Al-wadhih but he did not use learning media during the teaching-learning process, so students felt bored, such as: lack of attention on the subject matter and some of them also interrupted the class during the teaching-learning process. On the other hand, the boredom is also caused by the teacher not using appropriate techniques that are suitable for students in the teaching-learning process. This condition causes a lack of response from students during the learning process. Therefore, researcher will try to apply inductive methods using STAD techniques and question-and-answer card media to improve students' abilities in learning nahwu. The purpose of writing this thesis is to find out students’ responses to nahwu learning by applying the inductive method using STAD techniques and question-and-answer card media in nahwu learning, and to know their effectiveness in increasing students' abilities in nahwu learning. This study is an experimental study with a post-test only control group design. The population in this study were all level students at the Ulumul Quran boarding school while the sample was all students of class 2a as a control group and 2c as an experimental group totaling 44 people. The instruments used were post test and interview. To analyze the data in this study, testers used the t-test formula using the SPSS program. Based on the results of the study, the data shows that the use of inductive methods using STAD techniques and question-and-answer card media is effective in increasing the ability of students in learning nahwu in the Ulumul Qur'an boarding school. This is evident from the results of the value Sig.0.00 <0.05. This shows that the hypothetical (Ho) is rejected and the alternative hypothesis (Ha) is accepted.